2022
DOI: 10.3389/fnut.2022.1019615
|View full text |Cite
|
Sign up to set email alerts
|

A protein- and fiber-rich diet with astaxanthin alleviates high-fat diet-induced obesity in beagles

Abstract: Background and aimsOverweight or obesity is one of the most prevalent health burdens in companion pets and predisposes subjects to multiple comorbidities and reduced longevity. Dietary management and sufficient exercise are effective options for weight loss but challenged by modern lifestyle and calorie control-triggered malnutrition. Therefore, this study aimed to develop a formulated obesity control diet characterized by protein- and fiber-rich diet and supplemented with astaxanthin. We systemically evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…During feeding, it was found that dogs in the Le group could consume almost all of the 32 g/BW kg/d food, while dogs in the Me and He groups had varying degrees of leftovers, which may have been related to the fact that dogs can adjust their food intake according to their energy intake. A similar finding was obtained by Xue et al [14], where adult beagle dogs lost 15 to 25% of their body weight after eight weeks of consuming a diet with ME of 13.54 or 12.93 MJ/kg diet, while no significant changes were observed after 24 weeks of consuming a dietary ME of 15.07 MJ/kg diet.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…During feeding, it was found that dogs in the Le group could consume almost all of the 32 g/BW kg/d food, while dogs in the Me and He groups had varying degrees of leftovers, which may have been related to the fact that dogs can adjust their food intake according to their energy intake. A similar finding was obtained by Xue et al [14], where adult beagle dogs lost 15 to 25% of their body weight after eight weeks of consuming a diet with ME of 13.54 or 12.93 MJ/kg diet, while no significant changes were observed after 24 weeks of consuming a dietary ME of 15.07 MJ/kg diet.…”
Section: Discussionsupporting
confidence: 88%
“…The content of LDL-C in serum shows a significant positive correlation with the incidence of coronary heart disease, and it is an important index to evaluate the risk factors of individual coronary heart disease [74]. In canine obesity modeling and weight loss trials, high-fat diets were found to lead to a significant increase in serum CHO levels, while low-energy diets led to a decrease in CHO [13][14][15]75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that consistent overfeeding of dogs with a high-calorie Western diet (WD) can lead to MetS, regardless of the diet's composition (Moinard et al, 2020;Xue et al, 2022). However, these investigations in dogs have primarily focused on the metabolic issues associated with obesity (Tvarijonaviciute et al, 2012b;Peña et al, 2014;Moinard et al, 2020;Sun et al, 2023;Vecchiato et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that consistently overfeeding dogs with high-calorie Western diets (WDs) leads to obesity and MetS, regardless of the diet composition (Moinard et al, 2020;Xue et al, 2022). Indeed, prior studies investigating the effects of WDs in dogs have primarily focused on metabolic dysfunction related to obesity (Tvarijonaviciute et al, 2012b;Peña et al, 2014;Moinard et al, 2020;Sun et al, 2023;Vecchiato et al, 2023).…”
Section: Introductionmentioning
confidence: 99%